HUBUNGAN GAYA KEPEMIMPINAN KEPALA PUSKESMAS DENGAN KINERJA STAF DALAM PENCAPAIAN PROGRAM PUSKESMAS - Yulia M. Nur; Yade Kurnia Sari; Irwan Irwan (Ensiklopedia of Journal, 2022)
Leadership style is a way used by a leader in influencing the behavior of others. Leadership style is seen as one of the important predictors that affect performance. At the Parit Health Center in the last two years there has been a shift in leadership. This, affects the performance achievements obtained from year to year, and results in an indication of the cause of the decline in employee performance due to the different leadership styles of each leader. The purpose of the study was to determine the factors related to employee performance. This research method is quantitative using a quantitative descriptive design. The total population is 72 people, which is divided into 42 people with the status of civil servants and 30 people with the status of non civil servants using purposive sampling technique. Data processing was carried out univariate and bivariate. Data were analyzed by using Chi Square test with 95% confidence level. The results showed that 66.7% of the employees at the Parit Health Center liked the transactional leadership style, 59.7% of the employees liked the transformational leadership style, the situational leadership style was favored by the employees as much as 86.1%,. Statistical test results obtained transactional leadership style (p value = 0.161), transformational leadership style (p value = 0.140), situational leadership style (p value = 0.000). More than half of employees prefer transactional, transformational, and situational leadership styles. There is a significant relationship between employee performance and situational leadership style, and there is no significant relationship between employee performance and transactional leadership style and transformational leadership style.